2015
DOI: 10.5483/bmbrep.2015.48.6.031
|View full text |Cite
|
Sign up to set email alerts
|

FZD6 expression is negatively regulated by miR-199a-5p in human colorectal cancer

Abstract: Colorectal cancer (CRC), the third most common cancer worldwide, also has the highest rate of cancer-related morbidity and mortality. WNT signaling is initiated by binding of WNT to various receptors, including frizzleds (FZDs), and plays a critical role in CRC and other tumor development by regulating proliferation, differentiation, migration, apoptosis, and polarity. Among the members of the FZD family, FZD6 is broadly expressed in various tissues, and its overexpression has been reported in several cancers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
2
34
1
Order By: Relevance
“…Many studies have observed through mutagenesis experiments that several residues in the intracellular loops and the C-terminus of FZD play a prominent role in signaling (Cong et al, 2004;Wallingford and Habas, 2005). Kim et al (2015) found that the expression of FZD6 was increased in colorectal cancer (CRC) patients when compared to that in nontumor tissues. Furthermore, they discovered that FZD6 expression in CRC cells was negatively regulated by miR199a-5p (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have observed through mutagenesis experiments that several residues in the intracellular loops and the C-terminus of FZD play a prominent role in signaling (Cong et al, 2004;Wallingford and Habas, 2005). Kim et al (2015) found that the expression of FZD6 was increased in colorectal cancer (CRC) patients when compared to that in nontumor tissues. Furthermore, they discovered that FZD6 expression in CRC cells was negatively regulated by miR199a-5p (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2015) found that the expression of FZD6 was increased in colorectal cancer (CRC) patients when compared to that in nontumor tissues. Furthermore, they discovered that FZD6 expression in CRC cells was negatively regulated by miR199a-5p (Kim et al, 2015). In recent research, Corda et al (2017) observed that the Wnt receptor-encoding gene FZD6 is often duplicated in breast cancer and confers a higher risk of triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest that downregulation of miR‐199 is at least partly responsible for the observed induction of GCNT2 upon EMT of colon cancer cells. Consistent with these results, the levels of miR‐199 family members are downregulated in metastatic lesions in contrast with the primary tumor as seen in clinical samples of colon cancers, and miR‐199 suppresses colon cancer metastasis in vivo . It has been suggested that the miR‐199 family regulates the progression and metastasis of various cancers other than colon cancer, including liver, ovarian, prostate, and breast cancers .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that miRNAs function via regulating their target protein by binding to the 3’ untranslated regions (UTRs) of target messenger RNAs (mRNAs), resulting in mRNA degradation or the blockade of mRNA translation . Previously, miR‐199a‐5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia‐inducible factor 1 alpha (HIF‐1α), E‐cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin‐dependent kinase inhibitor 1C (P57, CDKN1C) …”
Section: Discussionmentioning
confidence: 99%
“…In present study, we showed that miR-199a-5p, frequently down- 19,20 Previously, miR-199a-5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia-inducible factor 1 alpha (HIF-1α), E-cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin-dependent kinase inhibitor 1C (P57, CDKN1C). [21][22][23][24][25][26][27][28][29] Clathrin is considered the prototype vesicle coat protein whose self-assembly mediates sorting of membrane cargo and recruitment of lipid modifiers. 30 In the past decades, most of studies were focused on clathrin mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%